Impact of Error of Prior-Period Earnings Forecast on Market Reaction to Management Earnings Forecast, and Different Types of Earnings Management - Ahmad Khodamipour (Shahid Bahonar University of Kerman, 2015)
The objective of this research is to investigate the reaction of market to the companies’ bad or good news, according to their earnings forecast in the last year, the managers’ inclination to keep or improve their fame in forecasting, and comparing managers' inclination towards upward earnings management with different types of earnings management and with respect to their last year forecast. To achieve this, the financial statements of 86 companies listed in the Tehran Stock Exchange between the years 1384-1390 were analyzed. To reach the research objective, the companies were categorized according to their last and current year forecasts, and their forecast contents. Then, considering the combined structure of the data, and using the statistical tests as T test, correlative coefficient of Pierson, and OLS, the hypotheses of the research were tested. The results showed that the market reaction to the earnings forecast with good (bad) news, when the last period forecast was optimistic (pessimistic),is more positive (more negative) than when the last period forecastis pessimistic (optimistic). Also, the results showed managers tend to be stable in earnings forecast. Additionally, the results showed the last period optimistic forecast could be considered the factor leading to upward earnings management in the current period.